(untitled) (Journal of Engineering, 2024)
Climate change poses a global challenge with profound repercussions on land cover, particularly affecting areas like Iraq due to decreased rainfall, rising temperatures, desertification, vegetation loss, and reduced river tiers attributable to weather change. This study investigates the impact of climate change on land cover in the Al-Hillah district of Babil province, Iraq, using remote sensing data and satellite imagery from Landsat 5 and 8 through the website of the US Geological Survey from 1995 to 2021. ArcMap 10.8 software program was employed to analyze and visualize these changes. The Al-Hillah district spans an area of 878 km2, encompassing built-up areas, agriculture areas, desert land, wetlands, and river surface areas. The analysis involved Landsat satellite imagery for 1999, 2015, and 2021. The findings display that Hilla District has skilled the outcomes of climate change, primarily manifested in the expansion of desert areas. In 1999, barren land covered 93 km2. It had increased to 183 square kilometers, resulting in rising temperatures and decreased rainfall about 2 degrees below the overall common. It has brought about a reduction in vegetation cover in an area of 196 square kilometers, compared to the year 1999 covered 45.6%.